Antibody Fragment and Affibody ImmunoPET Imaging Agents: Radiolabelling Strategies and Applications - Fu, Ruisi (ChemMedChem, 2018)
Antibodies have long been recognised as potent vectors for carrying diagnostic medical radionuclides, contrast agents and optical probes to diseased tissue for imaging. The area of ImmunoPET combines the use of positron emission tomography (PET) imaging with antibodies to improve the diagnosis, staging and monitoring of diseases. Recent developments in antibody engineering and PET radiochemistry have led to a new wave of experimental ImmunoPET imaging agents that are based on a range of antibody fragments and affibodies. In contrast to full antibodies, engineered affibody proteins and antibody fragments such as minibodies, diabodies, single‐chain variable region fragments (scFvs), and nanobodies are much smaller but retain the essential specificities and affinities of full antibodies in addition to more desirable pharmacokinetics for imaging. Herein, recent key developments in the PET radiolabelling strategies of antibody fragments and related affibody molecules are highlighted, along with the main PET imaging applications of overexpressed antigen‐associated tumours and immune cells.